Epigenetic aging upon allogeneic transplantation: the hematopoietic niche does not affect age-associated DNA methylation - Weidner, Carola Ingrid; Hahn, Michael; Ho, Anthony Dick; Dreger, Peter (Leukemia, 2015)
Leukemia is one of the leading journals in hematology and oncology. It is published monthly and covers all aspects of the research and treatment of leukemia and allied diseases. Studies of normal hemopoiesis are covered because of their comparative relevance.
published online 2 December 2014
Gesehen am 25.07.2017